Assessment of Productivity in the Development and Production Processes of Cricket Products and Their Impact on Thailand’s Manufacturing Sector - Phong-a-ran, Nathaporn; Tantrabundit, Pongsatorn (Engineering Access, 2026)
This research aims to evaluate the productivity in the development and production processes of cricket products and their impact on Thailand’s production sector. The advanced statistical tools were employed to conduct an in-depth assessment of these impacts using the Computable General Equilibrium Model (CGE). This model requires a database derived from Thailand’s Social Accounting Matrix (SAM). The study highlights the differences in various types of environmental costs, including energy costs, fertilizer and pesticide costs, and sanitary and similar services costs. The analysis results indicate that the development and production of cricket products affect Thailand’s top 10 production sectors. The sector most impacted was Sector 105: Iron and Steel, with a Multiplier value of 3.230, a Forward Linkage value of 0.970, and a real benefit of 0.148. The second most impacted was Sector 043: Canning and Preserving of Meat, with a Multiplier value of 2.614, Forward Linkage value of 0.785, and a real benefit of 0.700. The least affected sector among the top 10 was Sector 059: Coffee and Tea, with a Multiplier value of 2.272, Forward Linkage value of 0.683, and a real benefit of 0.706. The findings suggest that strategies to mitigate the negative impacts of energy production and consumption across all activities should follow the approach outlined in this research. Since no previous studies in Thailand have investigated this topic in such a manner, this research provides a critical foundation for future strategic planning